The degree of color change, rebound effect and sensitivity of bleached teeth associated with at-home and power bleaching techniques: A randomized clinical trial - Moghadam, Fatemeh Velayati; Majidinia, Sara; Chasteen, Joseph; Ghavamnasiri, Marjaneh (European Journal of Dentistry, 2013)
Aim: The purpose of the present randomized clinical trial was to evaluate the color change, rebound effect and sensitivity of at-home bleaching with 15% carbamide peroxide and power bleaching using 38% hydrogen peroxide. Materials and Methods: For bleaching techniques, 20 subjects were randomized in a split mouth design (at-home and power bleaching): In maxillary and mandibular anterior teeth (n = 20). Color was recorded before bleaching, immediately after bleaching, at 2 weeks, 1, 3 and 6 month intervals. Tooth sensitivity was recorded using the visual analog scale. The Mann-Whitney test was used to compare both groups regarding bleaching effectiveness (∆E 1 ), rebound effect (∆E 2 ) and color difference between the rebounded tooth color and unbleached teeth (∆E 3) while the Wilcoxon compared ∆E within each group. Distribution of sensitivity was evaluated using the Chi-square test (α =0.05). Results: There was no significant difference between groups regarding ∆E 1 and ∆E 3 (P > 0.05). Even though, ∆E 2 showed no significant difference between groups after bleaching as well as at 2 week, 1 month and 3 month follow-up periods (P > 0.05). Although, significant difference was found in ∆E 2 (P < 0.05 Mann-Whitney) between two methods after 6 months and a high degree of rebound effect was obtained with power bleaching. Within each group, there was no significant difference between ∆E 1 and ∆E 3 (P < 0.05 Wilcoxon). The distribution of sensitivity was identical with both techniques (P > 0.05).Conclusion: Bleaching techniques resulted in identical tooth whitening and post-operative sensitivity using both techniques, but faster color regression was found with power bleaching even though color regression to the baseline of the teeth in both groups was the same after 6 months.
Keywords: At-home bleaching; post-treatment sensitivity; power bleaching; tooth bleaching; tooth color regression